The Contributions of Ibn Jinni in the Science of Arabic Prosody and Rhyme - Mohamed Aziz Abdelmaksoud Sayed Ahmed; Ragab Ibrahim Ahmed Awad; Elsayed Mohamed Salem Alawadi (Indonesian Journal of Arabic Studies, 2021)
This study highlights Ibn Jinni's contribution to Arabic poetry,  especially in Arabic prosody (Al-'Arūd) and rhyme (Al-Qawafi) and to  describe his approach to compiling in Arabic prosody and rhyme. This study  is a qualitative research using descriptive and analytic methods. Description  is useful for describing the life of Ibn Jinni and his knowledge, then his contribution to the science of Arabic prosody and rhyme, and analysis is carried out to analyze the formulation of his approach in Arabic poetry, namely prosody and rhyme. The study found that Ibn Jinni's Prosodi concept as stated in his work entitled Al-'Arud agrees with the principles put forward by Al-Khalil bin Ahmed, especially in fifteen poetic meters (buḥur) and differ in one meter (bahar). Ibn Jinni has a thematic method in making poetry works, this makes it very easy for students to understand learning the prosody of Arabic poetry and rhymes.